THE STUDY OF THE PHYSICAL AND MECHANICAL PROPERTIES OF MATERIALS RAILROADS - Didik Sugiyanto; Besus Dwi Putranto (President University, 2016)
Abstract. This research is to determine the quality of the railway. As the object of research in this occasion was the train tracks acquired from the workshop of PT. Kereta Api Indonesia. As for the quality evaluation performed include hardness testing, testing of composition, tensile test and microstructure observation. After the base material subjected to the preliminary work, such as the manufacture of test specimens, prepared and then the specimens tested with testing tools for testing the hardness, chemical composition testing, tensile testing and testing microstructure. From the test results obtained with the price average hardness of the railroad is 281.7 HVN. The price of the average composition of the railroads alone amounted to 588.4%, while the average tensile strength of the railroad tracks of 0.04 N/mm², micro structure photograph taken with magnification 100x and 200x. From the test results note that the railroads have high ductility and toughness.Keywords. Physical, Mechanical, Railways, Microstructure